BARACK OBAMA’S IOWA CAUCUSES RHETORIC - Samuel Gunawan (Bahasa dan Seni: Jurnal Bahasa, Sastra, Seni, dan Pengajarannya, 2011)
This paper is to explore the depth of Barac Obama’s rhetoric in his Iowa Caucuses  Speech:  “Our  Time  for  Change  has  Come”.  Obama  displayed  his outstanding rhetorical craftmanship to drive irresistibly his power of persuasion in the  earliest  Democratic  Caucuses  in  the  whitest  state  of  Iowa  that  gave  him  a victory; thus the speech underscored the ground-breaking messages to the rest of the nation that America was ripe for an African-American President.